The Sims2 and Women’s IT Learning - Elisabeth R. Hayes; Elizabeth King; Jayne Lammers (Adult Education Research Conference, 2008)
The purpose of this study was to investigate how women who create custom content for The Sims2 acquire IT-related skills and knowledge. Interviews with twenty-six women suggest the importance of interest-driven learning, opportunities for horizontal as well as vertical learning, and the opportunity to develop “loose ties” with an extensive online social network of other Sims fans.
Keywords: women’s learning; computers; The Sims